Demographic-socioeconomic profile and sexual behavior of pregnant adolescents in a city in northeastern Brazil - Layla Melize Santos Menezes; Igor Soares Vieira; Leda Maria Delmondes Trindade (Acta Scientiarum. Health Sciences, 2016)
Adolescence pregnancy pictures the interaction between the exertion of sexuality and the reproductive life, as a process influenced by the historical and social context of the embedded person. This study aims to portray the demographic and socioeconomic profile and the sexual behavior of pregnant teenagers. It is a cross-sectional study accomplished at Family Health Units in a Brazilian northeast city. Participated in the study 50 adolescents between 13 and 19 years of age. It was adopted a survey with open and closed ended questions. Among the adolescents menarche occurred at an average of 11.68 years of age (pd = 1.3); 48% of them had their first sexual intercourse before 16 years-old (group average = 14.30 – dp = 1.71); the majority were primigravidae; abstained from alcohol ingestion during the gestational period and did not use birth-control methods; 98% had low family income. The pregnancy was a reason for school evasion. The knowledge of birth-control methods was not an impedible factor to the early pregnancy. The appropriation of the guideline for birth control has become one of the biggest difficulties in the basic health basic system to avoid unplanned pregnancy. In this situational context, there are sociocultural, political and economic factors involved.